MODEL PEMBELAJARAN RENANG (FH) BAGI SISWA PRASEKOLAH - WIDIASTUTI, WIDIASTUTI; HAMAMAH, FATIN (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
Abstract: The objective of this research is to generate a pool of learning model for students preschool. The method used in this research and development model from Borg and Gall. The Instruments used in the research of this model are questionnaires and pool Assesment instruments for students preschool used to collect data at the stage of : (1) analysis of needs; (2) the expert evaluation (initial product evaluation); (3) Tests small groups; (4) Friendlies large groups. Test the effectiveness of the model using the swimming assessment tests for students preschool to see improved results of swimming skills before applying the learning model created. Based on the results obtained between yield enhancement swimming skills before applying the learning model pool total 64.3%, and after being given treatment by using model new pool design researchers increased to 93.25%. Based on the research results can be concluded with the pool learning model for preschool students, students can learn effectively and efficiently. Key Word: Development, Model, Swimming Abstrak: Tujuan penelitian ini adalah untuk menghasilkan model pembelajaranrenang bagi siswa prasekolah. Metode yang digunakan dalam penelitian ini adalah model penelitian dan pengembangan (Research and Development) dari Borg dan Gall. Instrumen yang digunakan dalam penelitian model ini adalah kuisioner dan instrumen penilaian renang bagi siswa prasekolah yang digunakan untuk mengumpulkan data pada tahap: (1) analisis kebutuhan; (2) evaluasi ahli (evaluasi produk awal); (3) Ujicoba kelompok kecil; (4) Ujicoba kelompok besar. Uji efektifitas model menggunakan tes penilaian renang bagi siswa prasekolah dengan melihat peningkatan hasil keterampilan renang sebelum diterapkannya model pembelajaran. Berdasarkan hasil yang didapat peningkatan antara hasil keterampilan renang sebelum diterapkannya model pembelajaran renang total 64,3% dan setelah diberikan perlakuan dengan menggunakan model pembelajaran renang yang baru desain peneliti meningkat menjadi 93,25%. Berdasarkan hasil penelitian dapat disimpulkan dengan model pembelajaran renang FH bagi siswa prasekolah, siswa dapat belajar secara efektif dan efisien. Kata kunci: Pengembangan, Model, Renang